Paired Stimulation to Promote Lasting Augmentation of Corticospinal Circuits - Noam Y. Harel; Jason B. Carmel (Neural Plasticity)
After injury, electrical stimulation of the nervous system can augment plasticity of spared or latent circuits through focal modulation. Pairing stimulation of two parts of a spared circuit can target modulation more specifically to the intended circuit. We discuss 3 kinds of paired stimulation in the context of the corticospinal system, because of its importance in clinical neurorehabilitation. The first uses principles of Hebbian plasticity: by altering the stimulation timing of presynaptic neurons and their postsynaptic targets, synapse function can be modulated up or down. The second form uses synchronized presynaptic inputs onto a common synaptic target. We dub this a “convergent” mechanism, because stimuli have to converge on a common target with coordinated timing. The third form induces focal modulation by tonic excitation of one region (e.g., the spinal cord) during phasic stimulation of another (e.g., motor cortex). Additionally, endogenous neural activity may be paired with exogenous electrical stimulation. This review addresses what is known about paired stimulation of the corticospinal system of both humans and animal models, emphasizes how it qualitatively differs from single-site stimulation, and discusses the gaps in knowledge that must be addressed to maximize its use and efficacy in neurorehabilitation.